Unique Allelic eQTL Clusters in Human MHC Haplotypes. Issue 8 (1st August 2017) - Lam, Tze Hau; Shen, Meixin; Tay, Matthew Zirui; Ren, Ee Chee
Abstract: The control of gene regulation within the major histocompatibility complex (MHC) remains poorly understood, despite several expression quantitative trait loci (eQTL) studies revealing an association of MHC gene expression with independent tag-single nucleotide polymorphisms (SNPs). MHC haplotype variation may exert a greater effect on gene expression phenotype than specific single variants. To explore the effect of MHC haplotype sequence diversity on gene expression phenotypes across the MHC, we examined the MHC transcriptomic landscape at haplotype-specific resolution for three prominent MHC haplotypes (A2-B46-DR9, A33-B58-DR3, and A1-B8-DR3) derived from MHC-homozygous B-lymphoblastoid cell lines (B-LCLs). We demonstrate that MHC-wide gene expression patterns are dictated by underlying haplotypes, and identify 36 differentially expressed genes. By mapping these haplotype sequence variations to known eQTL, we provide evidence that unique allelic combinations of eQTL, embedded within haplotypes, are correlated with the level of expression of 17 genes. Interestingly, the influence of haplotype sequence on gene expression is not homogenous across the MHC. We show that haplotype sequence polymorphisms within or proximate to HLA-A, HLA-C, C4A, and HLA-DRB regions exert haplotype-specific gene regulatory effects, whereas the expression of genes in other parts of the MHC region are not affected by the haplotype sequence. Overall, we demonstrate that MHC haplotype sequence diversity can impact phenotypic outcome via the alteration of transcriptional variability, indicating that a haplotype-based approach is fundamental for the assessment of trait associations in the MHC.